PENGARUH CITRA PERUSAHAAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN SICEPAT EKSPRES POINT AGEN JATIASIH - Fahmy Ridho Akbary; Wiwik Rachmarwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The purpose of this study is to describe and analyze the effect of brand image and service quality on customer satisfaction at Sicepat Expres Point Agen Jatiasih. The independent variables are brand image and service quality, the dependent variable is customer satisfaction. Methods of data analysis with quantitative descriptive analysis using simple regression analysis and multiple linear regression. Sampling amounted to 100 respondents using the Random Sampling technique because the sampling of members of a population is done randomly without regard to the existing strata in the population. The results of the study can be concluded that: 1) Corporate image can increase customer satisfaction. 2) Service quality can increase customer satisfaction. 3) Improved company image and service quality can encourage increased customer satisfaction at SiCepat Ekspres Point Agen Jatiasih.